ANALISIS HARGA DAN NILAI TUKAR RUPIAH MEMPENGARUHI EKSPOR CENGKEH INDONESIA - Rusdin Mane (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
The purpose of this study to analyze the relationship between the variables Indonesian clove export price in international market , and GDP percapita of Indonesian clove importers State against Indonesian clove exports value in 2005-2014. The method of data analysis used in this study is Ordinary Least Square ( OLS ). The data used in this study is time series data from the years 2005-2014 ( 11 years ). The results showed that the two variables for the export of Indonesian clove in the International market and GDP percapita of Indonesian clove importers State simultaneously have a significant influence on the value of Indonesian clove exports in 2005-2014 . In Indonesian clove export price in the international market , and GDP percapita of Indonesian clove importers Country positive and significant effect on the export value of Indonesian clove years 2005-2014.